Stationary condition based performance analysis of the contraflow left-turn lane design considering the influence of the upstream intersection. (January 2021) - Wu, Jiaming; Liu, Pan; Zhou, Yang; Yu, Hao
Highlights: We prove that the performance of the CLL design would always converge to stationary conditions. Operational performance of the CLL design are evaluated based on stationary conditions. The residual queue phenomenon observed in field is well explained by theoretical models. Empirical optimization method for designing the contraflow lane is provided. Abstract: The present study conducted an operational performance analysis of the contraflow left-turn lane (CLL) design considering the influence of the upstream signalized intersection. The arrival distribution was generated using a platoon dispersion model. A stationary condition was defined, in which the performance of the CLL design remained stable in any stationary cycle. It has proved that the CLL system always converges to the stationary condition after a few cycles if the arrival distribution is fixed. In stationary cycles, the CLL design generates either recurrent and constant residual queues or no queues, depending on the arrival distributions of left-turning vehicles. Based on the stationary condition, analytical models were developed to estimate the operational performance for left-turns at signalized intersections with the CLL design. The results show that both the arrival pattern and the length of the contraflow lane can significantly influence the operational performance of the CLL design. The residual queues in the stationary condition could increase control delay significantly, leading to an overlong delay of the left-turning vehicles if the contraflow lane was not carefully designed. To this end, an empirical optimization method was proposed to minimize the control delay by optimizing the length of contraflow lanes and the offset between adjacent intersections. The research results can be directly employed by traffic engineers to optimize the CLL design and to estimate the operational performance of the signalized intersections with the CLL design.